If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 + x = 6 + 3x Solving 43 + x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 43 + x + -3x = 6 + 3x + -3x Combine like terms: x + -3x = -2x 43 + -2x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 43 + -2x = 6 + 0 43 + -2x = 6 Add '-43' to each side of the equation. 43 + -43 + -2x = 6 + -43 Combine like terms: 43 + -43 = 0 0 + -2x = 6 + -43 -2x = 6 + -43 Combine like terms: 6 + -43 = -37 -2x = -37 Divide each side by '-2'. x = 18.5 Simplifying x = 18.5
| 20m^2+25m^3= | | 16+7x=-40 | | 20*20-90+40= | | 5x^2-39x+29=0 | | Z=8(x+h) | | 0.00000458=(x^2)/3.9 | | 4.58*10^-6=[2x]^2/[3.9-x] | | X^2+85x-13800=0 | | 75p^3+50p^2-12p-8=0 | | (w+2)(w^2-3w+4)= | | 4.58*10^-6=(2x)^2/(3.9-x) | | 0.2x+0.3y=8 | | 3x+5x=1 | | 6X^2-10x-44x=0 | | 7/12•1/4=5 | | 9.40=x/(1.78-x) | | 100-0.24= | | 2x-18+x=15 | | 3x-50+8x=1300 | | 7890^1/6 | | B^3-4b^2-4b+16= | | 6x+11-29=732 | | 2/9=t/6 | | 18+5n-9=2n+3 | | (9.40)(1.78-x)=x | | 6x+11x-29=732 | | -12a^5+12a^4-4a^3= | | 10a+6a^3=0 | | 6/35b=36/5 | | -12a^5+8a^4-4a^3= | | 8/9x=-24 | | 5/2a=15 |